Adipokines in health and disease. (July 2015) - Fasshauer, Mathias; Blüher, Matthias
Highlights Adipose tissue secretes hundreds of adipokines that regulate important biological processes. Adipokines have the potential for future pharmacological treatment of a wide range of diseases. Adipokines may serve as markers for the early diagnosis of metabolic, cardiovascular, inflammatory, or malignant diseases.